Muji. - Kanai, Masaaki, ....-; Fukasawa, Naoto, ....-; Koike, Kazuko, ....- (New York : Rizzoli, 2010)
This fascinating monograph provides an unprecedented view into the inner workings of Muji, one of the most influential brands leading sustainable design. A prescient advocate of sustainable consumption and the matchless utility of good design, Muji's founding principle was to develop new and simple products at reasonable prices by making the best use of materials while minimizing their impact on the environment. From a humble inaugural line of eight products nearly three decades ago, the brand now sells nearly five thousand different products in hundreds of its own stores in Asia, Europe, and North America